Effect of Different Feed Additives on In Vitro Total Gas and Methane Production of Maize Hay and Bajra Straw based TMR - Patel, Sneh D; Garg, Deendayal; Savsani, Harish H; Sharma, Arun K; Sorathiya, Kalpesh K; Kalam, Sanket M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to investigate the efficacy of different feed additives in TMR on in vitro total gas production and  methane production. Total mixed ration was prepared by mixing of bajra straw, maize hay and concentrate in the ratio of 30:30:40.  Feed additives included in TMR on DM basis were Monensin 30 mg/kg (T1), cellulase (10,00,000 IU/g) 0.5% (T2), xylanase (1,50,000 IU/g)  0.5% (T3), chitosan 1% (T4), sodium bicarbonate 1% (T5), magnesium oxide 1% (T6), combination of sodium bicarbonate + magnesium  oxide 0.5% each (T7) and combination of cellulase + xylanase 0.5% each (T8). Rumen liquor was collected from two adult Surti goats  each 2 h post-feeding of TMR with above additives. Result revealed that in vitro total gas production (mL/200 mg) was significantly  (p
Keywords: Feed additives,; Methane production,; Total gas production; , Total mixed ration.